Consensus on the Rational Use of Antithrombotics in Veterinary Critical Care (CURATIVE): Domain 1—Defining populations at risk. Issue 1 (17th January 2019) - deLaforcade, Armelle; Bacek, Lenore; Blais, Marie‐Claude; Goggs, Robert; Lynch, Alex; Rozanski, Elizabeth
Abstract: Objectives: Thrombosis is a well‐recognized phenomenon in dogs and cats with a significant impact on morbidity and mortality. Despite growing awareness of thrombosis and increased use of antithrombotic therapy, there is little information in the veterinary literature to guide the use of anticoagulant and antiplatelet medications. The goal of Domain 1 was to explore the association between disease and thrombosis in a number of conditions identified as potential risk factors in the current veterinary literature, to provide the basis for prescribing recommendations. Design: A population exposure comparison outcome format was used to represent patient, exposure, comparison, and outcome. Population Exposure Comparison Outcome questions were distributed to worksheet authors who performed comprehensive searches, summarized the evidence, and created guideline recommendations that were reviewed by domain chairs. Revised guidelines then underwent the Delphi survey process to reach consensus on the final guidelines. Diseases evaluated included immune‐mediated hemolytic anemia, protein‐losing nephropathy, pancreatitis, glucocorticoid therapy, hyperadrenocorticism, neoplasia, sepsis, cerebrovascular disease, and cardiac disease. Settings: Academic and referral veterinary medical centers. Results: Of the diseases evaluated, a high risk for thrombosis was defined as dogs with immune‐mediated hemolytic anemia or protein‐losing nephropathy, cats with cardiomyopathy and associated risk factors, or dogs/cats with >1 disease or risk factor for thrombosis. Low or moderate risk for thrombosis was defined as dogs or cats with a single risk factor or disease, or dogs or cats with known risk factor conditions that are likely to resolve in days to weeks following treatment. Conclusions: Documented disease associations with thrombosis provide the basis for recommendations on prescribing provided in subsequent domains. Numerous knowledge gaps were identified that represent opportunities for future study.